Tick-Borne Viruses in Finland: Public Health Risks, Interventions and Research Insights - Alale, Theophilus Yaw; Klemola, Tero; Sormunen, Jani J.; Harvala, Heli; Kakkola, Laura; Tikkala, Jessica; Vesterinen, Eero J. (Wiley, 2026)
Ticks are obligate haematophagous arthropods that serve as vectors for diverse pathogens, including viruses, bacteria and protozoa. In Finland, the two primary tick species, Ixodes ricinus (castor bean tick) and Ixodes persulcatus (taiga tick), have been identified in the transmission of tick-borne viruses (TBV), notably tick-borne encephalitis virus (TBEV). This article reviews the epidemiology, public health interventions and research on ticks and TBVs in Finland over the past six decades (1960-2020), highlighting the marked increase in tick populations and the incidence of tick-borne diseases in humans. Factors contributing to these trends include climate change, shifts in land use and alterations in ecosystem dynamics, which have expanded the geographical range and seasonal activity of ticks. This evolving epidemiological landscape poses significant public health challenges, necessitating effective monitoring and intervention strategies. Current research efforts focusing on understanding the dynamics of tick populations, the distribution of TBVs, and the effectiveness of TBEV vaccination and general prevention measures are crucial for mitigating risks associated with tick-borne viral diseases in Finland.